Effectiveness of Computer-assisted Teaching Program and Lecture Method on the Effect of Junk Food on Health among the Adolescence in Selected Schools of Digboi, Tinsukia - Phukan Baruah, Aparajita; Chetia, Mayuri (International Journal of Nursing Research, 2024)
Aim: A comparative study was conducted to evaluate the effectiveness of computer-assisted teaching program and lecture methods on the effect of junk food on health among the adolescence in selected schools of Digboi, Tinsukia. Methodology: A descriptive comparative research design was adopted to collect data with the help of self-structured knowledge questionnaire from 60 adolescence selected using simple random method. The 60 adolescents were the students of Class VIII section (B) of Carmel School and Little Star Sr. Sec School, Digboi. Results: The collected data were arranged and analyzed and it was found that the post-test mean knowledge of students on “The ill effects of junk foods on health” gained through computer-assisted teaching is 19.83 with standard deviation of 2.49. The post-test mean knowledge of students on “The ill effects of junk foods on health” gained through lecture method of teaching is 16.5 with standard deviation of 2.38. It was found that the tabulated “t” value (2.00) is more than calculated “t” value (1), so the research hypothesis is accepted. The present study shows that the computer-assisted teaching method is more effective than lecture method the assumption of researcher that computer-assisted teaching method is more effective than lecture method is accepted. Conclusion: Based on the comparison of level of knowledge of the students gained through computer-assisted teaching and lecture method, it is concluded that computer-assisted teaching method is more effective than lecture method while providing knowledge to the adolescents.